2017
DOI: 10.1177/1591019917691252
|View full text |Cite
|
Sign up to set email alerts
|

Ruptured intracranial vertebral artery dissecting aneurysms: An evaluation of prognostic factors of treatment outcome

Abstract: Objective Intracranial spontaneous vertebral artery dissecting aneurysms commonly occur in the third to fifth decades of life, and are mostly associated with hypertension. Patients present with intracranial haemorrhage or thromboembolic events. Patients who present with intracranial haemorrhage carry about a 70% risk of recurrent bleeding. Patients with a posterior-inferior cerebellar artery (PICA) or ipsilateral dominant vertebral artery involve selecting which paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…In patients with severe SAH, the percentage with favorable outcome at 30 days has certainly increased during the past decade (31.7%, 31.3%, and 56.2%, respectively), and the recent data is more robust than that of another recent report. 14) This might be due to not only earlier treatment, as shown in Table 1 (80.0% of patients were treated within 24 h in JR-NET3), but also the increase in trained neuroendovascular specialists.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with severe SAH, the percentage with favorable outcome at 30 days has certainly increased during the past decade (31.7%, 31.3%, and 56.2%, respectively), and the recent data is more robust than that of another recent report. 14) This might be due to not only earlier treatment, as shown in Table 1 (80.0% of patients were treated within 24 h in JR-NET3), but also the increase in trained neuroendovascular specialists.…”
Section: Discussionmentioning
confidence: 99%
“…The destruction technique is the most effective method to prevent aneurysm rupture and rebleeding (2,3). The immediate obliteration rate is high.…”
Section: Discussionmentioning
confidence: 99%
“…The stent-assisted coiling technique extends the usage of endovascular treatment to VADA. Endovascular treatment includes destruction (parent artery occlusion) and reconstruction techniques (stent implantation with or without coiling) (25). However, there is currently controversy regarding the preferred treatment option.…”
Section: Introductionmentioning
confidence: 99%
“…The control injection (F-H) shows a less irregular shape of the affected V4 segment and a still markedly opacified pseudoaneurysm. (25,29). Prior experience has shown that the hemorrhageinduced platelet activation requires a tailored dosage based on response tests (e.g., Multiplate, Roche Diagnostics; VerifyNow, Accriva), with prasugrel being more efficient than ASA (30).…”
Section: Ischemic Complicationsmentioning
confidence: 99%